THE IMPACT OF ICT TRAINING AND MOTIVATION ON THE STUDENTS’ ACADEMIC PERFORMANCE - Suherman, Usep Deden (Universitas Labuhanbatu, 2025)
Purpose- ICT training and motivation are important in improving student competence in the learning process. This research is important to improve students' skills in understanding ICT. This study evaluates, individually and holistically, how training and accomplishment motivation affect students' competencies at FEBI UIN SGD Bandung.Methodology—Descriptive and verification methodologies are implemented in the investigation. The study was conducted on 100 pupils from FEBI UIN SGD Bandung. Saturated sampling methodologies were implemented to conduct the sampling. Data collection techniques used observation, questionnaires, and interviews. Multiple regression analysis is the methodology utilized for data analysis.Finding- The study's results suggest that student competency is influenced by training and achievement motivation, both individually and collectively. As a result, the competencies of FEBI UIN SGD Bandung students are influenced by ICT training and achievement motivation, and there is a correlation between increased enthusiasm for student accomplishment and improved competency. This illustrates that combining achievement incentives and ICT training improves students' competency at FEBI UIN SGD Bandung. The determinant value was 0.889, suggesting that training and motivation accounted for 88.9% of student competency. Concurrently, 11.1% was attributed to supplementary causes.Significance-This training will improve students' understanding of ICT, which helps improve students' academic achievement. Keywords : Training, Competence, Performance